IMPLIKASI TEORI PEMBELAJARAN FONOLOGI BAHASA PADA ANAK USIA DINI - Gunasari, Ni Putu Candra Gunasari (Universitas Tabanan, 2023)
Language is one of the fundamental abilities that a child must possess, in accordance with their developmental stages. The process through which a child begins to familiarize themselves with their environment through verbal means is commonly referred to as language acquisition in children. A child's initial language acquisition occurs when they acquire their first language. During the early stages of language acquisition, a child's focus is primarily on its communicative function. The understanding of the stages undertaken by children reveals that their language development progresses and evolves within a pattern and set of rules across these stages. This implies that the grammatical structure of a child's language can be considered relatively constant within a certain period since acquiring their first language.